PENGUATAN MODERASI BERAGAMA DIERA DIGITAL - Katuche, Greina (PARADOSI: Jurnal Teologi Praktika, 2025)
The digital era offers easy access to religious knowledge and platforms for interactive dialogue; however, it also serves as a fertile ground for extreme religious ideologies, radicalism, hate speech, and disinformation that threaten social cohesion. Without adaptive strengthening strategies, individuals and communities are vulnerable to narratives that can erode the values of tolerance, inclusivity, harmony, and diversity, which are crucial pillars in a pluralistic society. Therefore, strengthening religious moderation becomes imperative to stem destructive narratives and encourage peaceful, constructive religious practices that respect plurality. This article discusses the importance of strengthening religious moderation as an approach that balances freedom of expression with the values of tolerance in religious life. It does this through an analysis of various content on social media and by emphasizing the importance of digital literacy, the role of religious leaders, and the synergy between government, society, and digital platforms in creating a peaceful and inclusive digital space. The method used is a literature study to analyze prevailing phenomena, examine them, and provide insights into modernization in the digital era. The results of this research aim to instill positive values, educating the community to live peacefully, accept others' opinions, love one another, and live in unity.